2022
DOI: 10.54443/ijerlas.v2i1.171
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intelectual Capital and Islamicity Performance Index on Financial Performance in Sharia Banking in Indonesia

Abstract: This research was conducted with the aim of examining the effect of intellectual capital and the Islamic performance index on the financial performance of Islamic banking in Indonesia. The data used in this research is documentation data as much as 110 data which is the result of multiplication of 11 object observation data with 10 years observation period of Islamic banking financial reports for the period 2010-2019. This study uses the Moderation Regression Analysis research method with a static panel approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The findings revealed that VAIC had a significantly positive impact on ROA. This is also supported by research by Marzuki, et al (2022) which revealed that intellectual capital has a significant positive effect on financial performance.…”
Section: Introductionmentioning
confidence: 52%
“…The findings revealed that VAIC had a significantly positive impact on ROA. This is also supported by research by Marzuki, et al (2022) which revealed that intellectual capital has a significant positive effect on financial performance.…”
Section: Introductionmentioning
confidence: 52%
“…Between 1999Between -2002, four amendments to the Constitution were made to improve Indonesia's state system, including its institutional system. This was intended to provide limitations on state institutions' power by applying the principle of the separation of powers (distribution of power) (Marzuki, Heryansyah, & Hadi, 2023). The logical consequence is that there is no longer a superpower institution because the formulation of the distribution of power is based on a mechanism of mutual supervision and balance (checks and balances system) (Novreza, 2022).…”
Section: Introductionmentioning
confidence: 99%